The gene regulatory role of non-coding RNAs in non-obstructive azoospermia - Zhou, Guanqing; Zhang, Mimi; Zhang, Jingzhi; Feng, Yaofeng; Xie, Zhishen; Liu, Siyi; Zhu, Detu; Luo, Yumei (Frontiers in Endocrinology, 2022)
Non-coding RNAs are classified as small non-coding RNAs, long non-coding RNAs and circular RNAs, which are involved in a variety of biological processes, including cell differentiation, proliferation, apoptosis and pathological conditions of various diseases. Many studies have shown that non-coding RNAs are related to spermatogenesis, maturation, apoptosis, function, etc. In addition, the expression of non-coding RNAs in testicular tissue and semen of patients with non-obstructive azoospermia was different. However, the role of non-coding RNAs in the pathogenesis of non-obstructive azoospermia has not been fully elucidated, and the role of non-coding RNAs in non-obstructive azoospermia is rarely reviewed. Here we summarize the research progress of non-coding RNAs in the pathogenesis of non-obstructive azoospermia.